Involvement of functional autoantibodies against vascular receptors in systemic sclerosis. Issue 3 (15th November 2010) - Riemekasten, Gabriela; Philippe, Aurélie; Näther, Melanie; Slowinski, Torsten; Müller, Dominik N; Heidecke, Harald; Matucci-Cerinic, Marco; Czirják, László; Lukitsch, Ivo; Becker, Mike; Kill, Angela; van Laar, Jacob M; et al.
Abstract : Background: Systemic sclerosis (SSc) features autoimmunity, vasculopathy and tissue fibrosis. The renin-angiotensin and endothelin systems have been implicated in vasculopathy and fibrosis. A role for autoantibody-mediated receptor stimulation is hypothesised, linking three major pathophysiological features consistent with SSc. Methods: Serum samples from 478 patients with SSc (298 in the study cohort and 180 from two further independent cohorts), 372 healthy subjects and 311 control-disease subjects were tested for antibodies against angiotensin II type 1 receptor (AT1 R) and endothelin-1 type A receptor (ETA R) by solid phase assay. Binding specificities were tested by immunoprecipitation. The biological effects of autoantibodies in microvascular endothelial cells in vitro were also determined, as well as the quantitative differences in autoantibody levels on specific organ involvements and their predictive value for SSc-related mortality. Results: Anti-AT1 R and anti-ETA R autoantibodies were detected in most patients with SSc. Autoantibodies specifically bound to respective receptors on endothelial cells. Higher levels of both autoantibodies were associated with more severe disease manifestations and predicted SSc-related mortality. Both autoantibodies exert biological effects as they induced extracellular signal-regulated kinase 1/2 phosphorylation and increased transforming growth factor β gene expression in endothelial cells which could be blocked with specific receptor antagonists. Conclusions: Functional autoimmunity directed at AT1 R and ETA R is common in patients with SSc. AT1 R and ETA R autoantibodies could contribute to disease pathogenesis and may serve as biomarkers for risk assessment of disease progression.